2021
DOI: 10.1007/s00264-021-05219-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of acetabular screws in total hip arthroplasty and its influence on wear and periacetabular osteolysis in the long-term follow-up

Abstract: Purpose The cementless implantation of hip replacement cups may be performed with and without the additional use of acetabular screws. If the surgeon uses screws or not depends on variable factors. In general, the use of screws is intended to increase the primary stability of the cup. Whether screws increase the initial stability of the cup construct, or even reduce it in part, is the subject of considerable debate in the literature. It is also unclear whether the additional screws lead to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Als Versagensursachen von modularen Pfannensystemen kann dieser Abrieb sowohl auf der Seite der Gleitpaarung als auch durch das zusätzliche Interface zwischen azetabulärer Komponente (Metalback) und dem modularen Inlay (Backside Wear) auftreten [7]. Zentrale Öffnungen und Schraubenperforationen zementfreier modularer Pfannensysteme erlauben retrograd einen direkten Polyethylen-Knochen-Kontakt, in dessen Folge periazetabuläre Osteolysen und höhere Lockerungsraten publiziert wurden [8,9,10].…”
Section: Aseptische Lockerungunclassified
“…Als Versagensursachen von modularen Pfannensystemen kann dieser Abrieb sowohl auf der Seite der Gleitpaarung als auch durch das zusätzliche Interface zwischen azetabulärer Komponente (Metalback) und dem modularen Inlay (Backside Wear) auftreten [7]. Zentrale Öffnungen und Schraubenperforationen zementfreier modularer Pfannensysteme erlauben retrograd einen direkten Polyethylen-Knochen-Kontakt, in dessen Folge periazetabuläre Osteolysen und höhere Lockerungsraten publiziert wurden [8,9,10].…”
Section: Aseptische Lockerungunclassified
“…The use of screws in uncemented THA is intended to support and aid in the primary fixation of the press-fit cup; however, whether this is the case remains an unclear and debated topic in literature. 9 , 10 A meta-analysis performed by Fei et al 11 found screws had no significant impact on cup stability, however, a study by Tabata et al 12 indicated increased primary stability of the cup with the use of screws. Further, a registry study found that screws did not provide protection against acetabular cup loosening but also did not have any long-term negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Additional screw fixation is often applied to improve acetabular cup stability during initial fixation [5]. Although it may not reduce the need for future revision or reoperation [6], there are reports of periacetabular osteolysis owing to the infiltration of joint fluid and polyethylene wear particles through the screw hole that may lead to loosening of the cup in the long term [5,[7][8][9]. Therefore, the long-term effectiveness of screws in acetabular cup THA remains unclear.…”
Section: Introductionmentioning
confidence: 99%